(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
It seems that there is a well-high harmony of opinion within the critical portion of the Israeli scholars, according to which peaceful coexistence is, indeed, the only enlightened educational solution for the Israeli-Palestinian conflict. However, one cannot be sure that this harmony is not somewhat the harmony of spheres to the ears of mainstream Israelis. My claim is that a coexistent education is impuissance at best, or perpetuation of the Israeli situation at worst, as, in the end, it rather accepts, consciously or unconsciously, the fundamentals behind the hegemonic Zionist ideology. That is, the exclusivist unmediated Jewish patriotism, which taking apart the mainstream Israelis from the Palestinians, and subsequently put them at a distance. A distance which is the real driving force and the quintessence of the conflict.